Measuring systemic financial stress and its risks for growth - Sulkhan Chavleishvili; Manfred Kremer (European Central Bank (ECB), 2023)
This paper proposes a general statistical framework for systemic financial stress indices which measure the severity of financial crises on a continuous scale. Several index designs from the financial stress and systemic risk literature can be represented as special cases. We introduce an enhanced daily variant of the CISS (composite indicator of systemic stress) for the euro area and the US. The CISS aggregates a representative set of stress indicators using their time-varying cross-correlations as systemic risk weights, computationally similar to how portfolio risk is computed from the risk characteristics of individual assets. A boot-strap algorithm provides test statistics. Single-equation and system quantile growth-at-risk regressions show that the CISS has stronger effects in the lower tails of the growth distribution. Simulations based on a quantile VAR suggest that systemic stress is a major driver of the Great Recession, while its contribution to the COVID-19 crisis appears to be small.
Keywords: C14; C31; C43; C53; E44; G01; 330; Financial crisis; Financial stress index; Macro-financial linkages; Quantile VAR; Systemic risk